Kebijakan Kriminalisasi Dalam Perlindungan Merek di Indonesia Berdasarkan Undang-Undang Nomor 15 Tahun 2001 Tentang Merek - Tuffemili, Freddy; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Against brand counterfeiting lot happening in recent years. Such violations include counterfeit goods (KW) communication devices such as mobile phones, android, wireless, walkie-talkies, smart phones, modems. tort against the brand is a serious crime. The purpose of this thesis, namely the first, the history of legislation in the field of brand, second, the crime of counterfeiting brands according to Law No. 2001 on Marks .15.This type of research is classified normative legal research. The source of data is secondary data which is divided into 3 (three), which is the primary legal materials, secondary and tertiary. In the data collection methods of documentary study literature or studies. Data were analyzed quantitatively, the descriptive outline of the data obtained. In drawing conclusions using deductive method of thinking, the way of thinking which draw a conclusion from a statement or proposition of a general nature be a statement or a case of a special nature.From the research, the First, the setting of the brand in Indonesia, has undergone several changes of laws include Act No. 21 of 1961, repealed and replaced by Act No. 19 of 1992 on Marks, then change and improvement as outlined in Law Number 14 Year 1997 regulation on the provisions of this brand then undergoes profound changes, with the ratification of Law No. 15 of 2001 regarding Mark, Second, setting the crime of counterfeiting of brand communication tools based on Law No. 15 of 2001 on brand Trademark Counterfeiting crime Settings Communication Equipment Based on Law No. 15 of 2001 on Marks, published in the Trademark Act classifies the entire crime referred to in the law as to a complaint, not a regular offense. This means that the criminal provisions in the Act Brand enacted after a report from someone who harmed the actions of others that related to a complaint any police investigation can be stopped only by the withdrawal of the police report mentioned by the complainant to the extent not examined in court.Key Word : Counterfeiting–Brand